An empirical analysis of beliefs about climate change challenges - Martino, Gaetano; Ventura, Flaminia; Diotallevi, Francesco (Italian Review of Agricultural Economics, 2016)
In the last decades, one of the main efforts of the Common Agricultural Policy was to promote a better use of natural resources in agricultural and food production. The adoption of environment-friendly technology depends in turn on farmers beliefs in the different solutions offered by the knowledge-based systems. In this context, farmers beliefs are recognized to be the critical drivers of the possibilities of adopting new technologies in the field of climate change mitigation. This study considers the beliefs as drivers of the farmers evaluation of the possibility to contribute to climate change mitigation and frame them in wider conceptual framework of institutional change. The objective of the study is to address the question on whether or not the farmer beliefs about technology influence the potential farming activities contributions to mitigation. The results of the empirical analysis confirms the role of the beliefs and of their institutional dimensions.